(untitled) (Research, Society and Development, 2020)
Introduction: The training of nurses in care for the individual Trans, shows us the need for some changes in professional practice since it is notable the little intimacy about the demands of this population. Objective: To survey what scientific production reveals about nursing care for the Trans public. Method: Integrative review of a qualitative approach. Results: After searching the database, As researched in the virtual health library - VHL and Public Medline (PubMed) in the LILACS (Latin American and Caribbean Literature in Health Sciences) databases, BDENF (Nursing database) ) and MEDLINE (Medical Literature Analysis and Retrieval System Online) The result is that there is no preparation to better assist the Trans population in the training of nurses, there is also little scientific production about this care, in addition to little promotion of the National Policy LGBT Integral Health Program in the training of this professional. Final considerations: The construction of a dialogue about the health needs of the trans individual needs to exist within the training of the nurses professional to prepare him/her to meet the care demands concerning nursing care, so programmatic contents are suggested to be applied in the training of nurses.